Pengaruh Otonomi Daerah, Pengeluaran Pemerintah, dan Tenaga Kerja terhadap Produk Domestik Regional Bruto (PDRB) Provinsi Bali tahun 1993-2012 - Agustina, Melasia; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 8, Agustus 2014 (pp.337-394), 2014)
Implementation of regional autonomy gives an opportunity for each region to improve the region’s revenue potential through the development of elapsed areas. Utilization of local resources can effectively spur economic activity in the region. Which in turn can improve the welfare of society. This study aims to determine the effect of simultaneous and partial autonomy, government spending, and labor to the Gross Regional Domestic Product of Bali in 1993-2012. Data used in this study is secondary data obtained from BPS. The analysis technique used to solve the problem in this research is the multiple linear regression analysis model. The result showed that simultaneous decentralization, government spending, and labor significantly influence the Gross Regional Domestic Product of Bali from 1993 to 2012. Partially government spending and labor have positive and significant, whereas no significant effect of regional autonomy.   Keyword : autonomy, government spending, labour, gross regional domestic product.